2009
DOI: 10.1111/j.1474-9726.2008.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular senescence in pretransplant renal biopsies predicts postoperative organ function

Abstract: SummaryOlder and marginal donors have been used to meet the shortfall in available organs for renal transplantation. Post-transplant renal function and outcome from these donors are often poorer than chronologically younger donors. Some organs, however, function adequately for many years. We have hypothesized that such organs are biologically younger than poorer performing counterparts. We have tested this hypothesis in a cohort of preimplantation human renal allograft biopsies ( n = 75) that have been assayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 30 publications
1
70
1
Order By: Relevance
“…Higher levels of p16 ink4a expression are associated with poorer function as measured by serum creatinine and urine proteinto-creatinine ratio (UPCR) levels at 6 months and 1 year posttransplant. 29,30 This correlates with the findings from this study that control mice that presented with higher serum creatinine levels also exhibited higher expression levels of p16 ink4a . Within the time course of this experiment, we would have expected to see an initial rise in p21, peaking by day 7, then reducing to control levels by day 14, with a correlated increase in p16 ink4a expression from day 7, peaking at day 14.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Higher levels of p16 ink4a expression are associated with poorer function as measured by serum creatinine and urine proteinto-creatinine ratio (UPCR) levels at 6 months and 1 year posttransplant. 29,30 This correlates with the findings from this study that control mice that presented with higher serum creatinine levels also exhibited higher expression levels of p16 ink4a . Within the time course of this experiment, we would have expected to see an initial rise in p21, peaking by day 7, then reducing to control levels by day 14, with a correlated increase in p16 ink4a expression from day 7, peaking at day 14.…”
Section: Discussionsupporting
confidence: 89%
“…We and others have previously demonstrated that p16 ink4a is a superior marker for the assessment of renal function. 4,5 p16 ink4a expression was significantly lower in the kidneys of PC-treated mice than those mice treated with saline ( p = 0.009; Fig. 2A, 2B).…”
Section: Pcs Facilitate Repair Of Kidney Tissue Damage Following I/r mentioning
confidence: 88%
See 1 more Smart Citation
“…Notably, deaths due to chronic kidney disease have increased globally, despite significant decline in other aetiologies (Christopher & Murray, 2015). This is pertinent to researchers investigating ageing, as accelerated cellular and physiological ageing are underlying components of renal dysfunction (Kooman, Kotanko, Schols, Shiels, & Stenvinkel, 2014; McGlynn et al, 2009; Schmitt, Susnik, & Melk, 2015), where systemic differences are layered on top of the dysregulated ageing process and patients show a higher incidence of mortality in comparison to healthy chronologically age‐matched individuals. As the prevalence of CKD parallels an increased prevalence in type 2 diabetes, obesity and a sedentary lifestyle (Stengel, Tarver‐Carr, Powe, Eberhardt, & Brancati, 2003), an allostatic outcome reflecting the “burden of life style” may be present next to the renal dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, these expression dissimilarities were recognized by the time of procurement (before cold ischemia) in brain-death donor kidneys, and after first warm ischemia in deceased donor kidneys (21). In addition, in targeted studies (22)(23)(24), mRNA levels of cyclin-dependent kinase inhibitor 2A (CDKN2A) in pretransplant kidney biopsies, one of the markers of cellular senescence, was documented as the most solid posttransplant predictor of serum creatinine at 6 months and one year in confront with clinical factors as age of donor and cold ischemic time. In addition, CDKN2A was also a solid predictor of DGF (24).…”
Section: Tissue Biomarkersmentioning
confidence: 99%